2018
DOI: 10.1002/nau.23807
|View full text |Cite
|
Sign up to set email alerts
|

Midurethral support is also necessary for reflex closure of the urethra

Abstract: Continence is a result of passive as well as active urethral closure mechanisms. The most important factor in female continence seems to be the proper functioning of an active reflex urethral closing mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Ensuring the proper functional urethral length is the key factor in female continence. The thickest part of the urethral sphincter in the whole of the urethra is the middle part, which is the part mainly controlling urinary continence [ 37 , 38 , 39 ]. Tension-free middle urethral suspension for the treatment of SUI aims to ensure the effective functional length of the middle of the urethra when abdominal pressure increases and effectively improve the patient’s urinary continence function [ 38 ].…”
Section: Anatomical Factors Of the Urethra Itselfmentioning
confidence: 99%
See 1 more Smart Citation
“…Ensuring the proper functional urethral length is the key factor in female continence. The thickest part of the urethral sphincter in the whole of the urethra is the middle part, which is the part mainly controlling urinary continence [ 37 , 38 , 39 ]. Tension-free middle urethral suspension for the treatment of SUI aims to ensure the effective functional length of the middle of the urethra when abdominal pressure increases and effectively improve the patient’s urinary continence function [ 38 ].…”
Section: Anatomical Factors Of the Urethra Itselfmentioning
confidence: 99%
“…The thickest part of the urethral sphincter in the whole of the urethra is the middle part, which is the part mainly controlling urinary continence [ 37 , 38 , 39 ]. Tension-free middle urethral suspension for the treatment of SUI aims to ensure the effective functional length of the middle of the urethra when abdominal pressure increases and effectively improve the patient’s urinary continence function [ 38 ]. Pelsang et al [ 40 ] showed that when the abdominal pressure of SUI patients increased, the bladder neck and the proximal urethra moved downward, forming a funnel shape and leading the relative length of the functional urethra to become shorter, thus causing urethral resistance, and the hydrostatic pressure of the urethra decreased, which can easily contribute to the occurrence of urinary incontinence.…”
Section: Anatomical Factors Of the Urethra Itselfmentioning
confidence: 99%
“…Urethral bulk injection therapy is an alternative noninvasive, ambulatory treatment that involves injecting a bulk material transurethral or periurethral, with or without urethroscopic view, in the mucosa of the urethra between the mid‐urethra and bladder neck. The injected material gives resistance to the urine flow and thereby aims to prevent leakage of urine, although it is hypothesized that mid‐urethral support is needed for the closure mechanism of the urethra as well 5 . To date, randomized controlled trials comparing bulk injection therapy with other surgical options show significant lower objective cure rates regarding urethral bulk injection therapy 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Mid-urethral support is important for reflex closure of the urethra. 4 Another factor may therefore be (mid-)urethral support bulk provides, reducing hypermobility of the urethra often seen in women with SUI and improving sphincter function.…”
Section: Introductionmentioning
confidence: 99%